2012
DOI: 10.1161/circinterventions.112.972430
|View full text |Cite
|
Sign up to set email alerts
|

A Validated Risk Score to Predict Outcomes after Carotid Stenting

Abstract: Background-Periprocedural outcome has been extensively investigated in patients undergoing carotid artery stenting.However, risk factors contributing to long-term mortality have not been comprehensively assessed. We aimed to establish a validated clinical risk score for long-term mortality in patients after carotid artery stenting. Methods and Results-Two independent cohorts after successful carotid artery stenting (602 and 552 patients) were prospectively investigated. Multivariable Cox regression and bootstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Coagulopathy was also identified as an independent risk factor for acute renal failure and multiorgan failure (36) . PT was found to be the independent predictor of long-term mortality in patients undergoing carotid stenting (37) . In that study, PT remained a significant predictor for mortality after excluding patients with (stopped) oral anticoagulation.…”
Section: Discussionmentioning
confidence: 88%
“…Coagulopathy was also identified as an independent risk factor for acute renal failure and multiorgan failure (36) . PT was found to be the independent predictor of long-term mortality in patients undergoing carotid stenting (37) . In that study, PT remained a significant predictor for mortality after excluding patients with (stopped) oral anticoagulation.…”
Section: Discussionmentioning
confidence: 88%
“…Most studies to date have focused on the short-term outcomes of CAS patients, and long-term survival data are not numerous in the literature. In this study, the annual mortality rate was 6.4%, compared to 2.3% in the TARGET-CAS trial (mean age at CAS 65 years, mean follow-up: 23 months) [ 16 ], 3.4% in the multi-center European study (mean age at CAS 72 years, mean follow-up: 32 months) [ 17 ], 3.6% in the Italian study (mean age at CAS 71.5 years, mean follow-up 33 months) [ 18 ], and 5.4% in the Austrian trial (Linz group: mean age at CAS 71 years, median follow-up: 6.5 years) [ 19 ]. These comparisons suggest that the patients included in our study were at high risk for long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…Hoke et al . stratified CAS patients into tertiles according to weighted risk score and observed 5-year survival of 91%, 73%, and 48% in the first, second, and third tertiles, respectively [ 19 ]. Our patients had a 5-year survival rate of 70% and 76% in the MVD and non-MVD groups, respectively, which correlates with the second tertile of the above-mentioned study.…”
Section: Discussionmentioning
confidence: 99%
“…Likelihood of brain damage after CAS procedure depends on various factors, as data from various researchers indicate. Some investigators have shown the connections of early post procedural brain ischemic abnormalities with male gender [32,40], others -with older age [41], yet otherswith concomitant illnesses such as ischemic cardiac disease or diabetes [42], with certain peculiarities of anatomy and physiology of the body and the type of the aortic arch [33,34], and also with such risk factors as overweight/obesity, dyslipidemia and smoking [39,43]. Results of our study confirm other researchers' findings that the type of the aortic arch and application of certain systems of protection during the CAS procedure may determine worse early results after the CAS procedure and a more frequent worse outcome [44].…”
Section: Discussionmentioning
confidence: 99%